Self-Assembly of Nanoporous Silica Particles for Tagging and Sensing Applications - Kalaparthi, Vivekanand. (2017)
Abstract: Meso(nano)porous silica particles are of broad interest for many photonic applications, filtration, drug delivery, catalysis. Through a self-assembly process, one can achieve silica particles spanning in size from microns to tens of nanometer. In the early stage of self-assembly it is observed that 20-50 nm seed particles are formed with hexagonally packed open cylindrical nanochannels. However, what is unknown is how these seed-like particles aggregate and self-align their pores to form final multi-micron particles with self-sealed channels extended over the entire particle.. In the course of this research, we examined the assembly mechanism of mesoporous multi-micron size silica particles with long cylindrical pores of 4-5 nm in diameter.We further showed that the observed alignment of channels was thermodynamically favored by a decrease in the Gibbs free energy of the particles. Besides a fundamental understanding of the mechanism of morphogenesis and pore formation, we demonstrated that the results of this finding could be further extended to make multi-hierarchical, sponge-like structured particles. Such particles can be used for controlledrelease of various substances from semi-sealed cylindrical pores of the particles. Next, we focused on fluorescent silica particles formed by loading fluorescent dye inside the sealed nanochannels. Such photonic materials find applications in tagging/labeling of biological cells and as tracers. Previous works have shown that physical encapsulation of dye leads to ultrabright properties. However, the nature of ultrabrightness was unclear. Here we investigated the ultrabrightness phenomenon observed for dye hosting nanoparticles and micron size discoid-shaped particles. This investigation revealed that the ultrabrightness was caused by a specific hydrophobic nanoscale environment around the encapsulated dye molecules offered by surfactant molecules inside the nanochannels. This environment allows dye molecules to be packed in concentrations which are not attainable for free dye without quenching of fluorescent properties. The close proximity of the encapsulated dye molecules to each other allows them to utilize the quantum energy transfer between dyes with complementary emission and absorbance (donor-acceptor pairs), which is called Forster resonance energy transfer (FRET). Using FRET, we demonstrated ultrabright temperature nanosensor (nanothermometers). Nanothermometers were assembled by encapsulating two different dyes, in which one of them was temperature-sensitive while the other acted as reference. The FRET based sensor comes with an advantage where a single excitation source can be used to excite the particle fluorescence. To demonstrate the working principle of nanothermometers, a 3D temperature distribution around a hot wire immersed in hydrogel-particles system was measured. The observed experimental results were validated by computation.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Igor Sokolov.; Committee: Jeffrey Guasto, Marc Hodes, Fiorenzo Omenetto, and Mingdi Yan.; Keyword: Mechanical engineering.